2018
DOI: 10.1111/pirs.12244
|View full text |Cite
|
Sign up to set email alerts
|

Internet infrastructure and regional convergence: Evidence from Turkey

Abstract: This study presents novel evidence regarding the role of regional internet infrastructure in reducing regional per capita income disparities. We base our study on the assumptions that (1) the diffusion of information homogenizes regional economies through reducing the dissimilarities in institutions and culture, and (2) the telecommunication capacity, represented by the internet infrastructure of a region, facilitates this flow of information. Using the data from the 26 statistical NUTS‐2 regions of Turkey for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 79 publications
3
14
0
Order By: Relevance
“…Estimation of elasticity parameter of the growth of real GDP per capita to internet user ratio is positive. This is in line with research conducted by Celbis and Crombrugghe (2016). At the level of the APT area as whole in the 2001-2014 period, an increase in the internet users ratio will increase the growth of real GDP per capita.…”
Section: The Effect Of Internet User Ratios On the Growth Of Real Gdpsupporting
confidence: 71%
“…Estimation of elasticity parameter of the growth of real GDP per capita to internet user ratio is positive. This is in line with research conducted by Celbis and Crombrugghe (2016). At the level of the APT area as whole in the 2001-2014 period, an increase in the internet users ratio will increase the growth of real GDP per capita.…”
Section: The Effect Of Internet User Ratios On the Growth Of Real Gdpsupporting
confidence: 71%
“…In particular, Grubesic and Murray () note the dramatic differences in broadband Internet competition between rural and urban areas, while Grubesic () identifies core and periphery regions of broadband. Others have suggested that the diffusion of Internet infrastructure may serve to reduce income inequality (Celbis & Crombrugghe, ). Spatial econometric techniques have commonly been applied in this arena, since acknowledging the spatial nature of broadband is an important component of developing an appropriate theoretical model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When only lag GDP per capita, population growth and FDI are included as in column (2), the convergence speed is 11.2 percent which implies that it would take 6.2 years for Vietnamese provinces to close half the gap to their steady states. This speed is relatively high compared to the commonly founded 2 percent in previous literature (Abreu et al, 2005) but is consistent with what has been observed among provinces in other developing countries such as China (Hong and Sun, 2011) or Turkey (Celbis and Crombrugghe, 2016). Interestingly, the significant estimation of FDI capital confirms its positive impact on provincial income.…”
Section: Fdi Technology Levels and Income Convergencesupporting
confidence: 88%